Emergence of Fosfomycin Resistance by Plasmid-Mediated fos Genes in Uropathogenic ESBL-Producing E. coli Isolates in Mexico - Mario Galindo-Méndez; Humberto Navarrete-Salazar; Francisco Baltazar-Jiménez; Eduardo Muñoz-de la Paz; María Fernanda Sánchez-Mawcinitt; Alexis Gómez-Pardo; Elvira Garza-González; Luis Alfredo Ponce-; Rafael Franco-Cendejas; Rayo Morfín-Otero; Fabián Rojas-Larios; Juan Pablo Mena-Ramírez; et al. (MDPI AG, 2022)
Fosfomycin is currently a viable option against urinary tract infections, particularly against extended-spectrum β-lactamases (ESBL)-producing E. coli, due to its unique mechanism of action and its low resistance among bacteria. The objective of this study was to investigate two of the three most common mechanisms of resistance against this antibiotic among 350 ESBL-producing E. coli strains isolated from the urine of Mexican patients. The prevalence of fosfomycin resistance in our study was 10.9% (38/350). Of all resistant isolates analyzed, 23 (60.5%) were identified as fos-producing organisms, with 14 strains carrying fosA3 and 9, fosA1. Additionally, 11 (28.9%) fosfomycin-resistant isolates presented resistance due to impaired antibiotic transport and 8 (21.0%) both mechanisms. No resistance mechanism investigated in the study was found on 12 strains. All 38 confirmed ESBL-producing isolates carried a blaCTX-M subtype, 36 (94.5%) belonged to the O25b-ST131 clone, and all of them were able to transfer the fosfomycin resistance trait to recipient strains horizontally. This is the first study in Mexico demonstrating a plasmid-mediated fosfomycin resistance mechanism among clinical E. coli strains. Since our results suggest a strong association among fos and blaCTX-M genes and ST131 clones in uropathogenic E. coli, plasmid-mediated fosfomycin resistance should be closely monitored.